RFID Application in Developing Key Management System - Ismail, Syazirawati; Mustafa, Mohamad Zaid; Ahad, Rosnee (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: The RFID application in the lock management system is a lock box product with an automatic control system that works to store and return the key. There are three main objectives namely designing, developing, and testing the functionality of RFID applications in key management systems. The system consists of two main parts namely hardware and software. The hardware consists of an Arduino nano microcontroller, solenoid lock, LCD display, ultrasonic detector, RFID reader and power supply circuit. The RFID used is a passive type, which are lighter and less expensive than active tags. During the development of this project, the research methodology used as a guide is the Design Thinking model which involves five phases namely empathise, define, ideate, prototype and test. In addition, expert evaluations about the functionality of the product indicated this product works well. However, some improvement in terms of reporting and monitoring of key records using the medium of IoT, also the use of ultrasonic detector and keypad were also suggested for the betterment of the product. Keywords: RFID, Automatic control system, design thinking model, Arduino Nano